PELAKSANAAN PEMBINAAN KEPRIBADIAN PADA ANAK DIDIK PEMASYARAKATAN (STUDI DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II LOMBOK TENGAH) - Baiq Linda Ayu Kusumawardani; Rispawati Rispawati; Yuliatin Yuliatin (Indonesian Publication Center, 2020)
This study aims to describe the implementation of personality coaching in correctional students and the factors that affect the implementation of personality development in correctional students in LPKA Class II, Central Lombok. This research uses a qualitative approach with descriptive methods. The subjects and informants of this study were determined based on the criteria. The data that has been collected is analyzed descriptively through data reduction steps, data presentation, and drawing conclusions. The findings in this study are the implementation of personality development in correctional students in LPKA Class II Lombok Tengah includes: the implementation of fostering the devotion to God Almighty, awareness of the nation and state, intellectuals, attitudes and behavior, physical and spiritual health, legal awareness and healthy reintegration. with the community. Internal factors for the implementation of personality coaching include coaching facilities, human resources, the quality of the personality development program, the cooperative attitude of correctional students, and sufficient budget funds. The external factor in the implementation of personality development in cooperation with related agencies.